Civic Engagement in Times of Crisis: How did Romanian Emerging Adults Engage? - Bianca V. MARINICA; Oana NEGRU-SUBTIRICA (Studia Universitatis Babeş-Bolyai. Psychologia-Paedagogia)
The COVID-19 pandemic created a unique context in which community engagement was necessary for handling the crisis and emerging adults had a reduced risk in the face of the virus. Therefore, this paper aimed to take an in-depth look at the ways in which emerging adults engaged in their communities. Inductive thematic analyses conducted on a sample of 86 Romanian emerging adults (Mage= 23.38, SDage= 2.71) revealed two main themes: General engagement (subthemes Passing on knowledge, Helping disadvantaged groups, Organizing events, and Political engagement), and Pandemic-related engagement (subthemes Initiatives directly related to the COVID-19 virus, and Initiatives related to the wider impact of the COVID-19 pandemic). Results show that most Romanian emerging adults engaged in activities not directly related to handling the crisis and identify one worryingly unpopular form of engagement: political engagement.